Is severe maternal morbidity a risk factor for postpartum hospitalization with mental health or substance use disorder diagnoses? Findings from a retrospective cohort study in Maryland: 2016–2019 - Carrie L Wolfson; Jessica Tsipe Angelson; Andreea A Creanga (Maternal Health, Neonatology and Perinatology)
Abstract Background Perinatal mental health conditions and substance use are leading causes, often co-occurring, of pregnancy-related and pregnancy-associated deaths in the United States. This study compares odds of hospitalization with a mental health condition or substance use disorder or both during the first year postpartum between patients with and without severe maternal morbidity (SMM) during delivery hospitalization. Methods Data are from the Maryland’s State Inpatient Database and include patients with a delivery hospitalization during 2016–2018 (n = 197,749). We compare rate of hospitalization with a mental health condition or substance use disorder or both at 42 days and 43 days to 1 year postpartum by occurrence of SMM during the delivery hospitalization. We use multivariable logistic regression to derive the odds of hospitalization with each outcome for patients by SMM status, adjusted for patient sociodemographic characteristics, presence of mental health condition or substance use disorder diagnoses during the delivery hospitalization, and delivery outcome. All SMM, mental health conditions, and substance use disorders are identified using ICD-10 diagnosis and procedure codes. Results Overall, 5,793 patients (2.9%) who delivered during 2016–2018 experienced hospitalization in the year following delivery. Among these patients, 24.3% (n = 1,410) had a mental health condition diagnosis, 10.6% (n = 619) had a substance use disorder diagnosis, and 9.8% (n = 570) had co-occurring mental health condition and substance use disorder diagnoses. Patients with SMM had 3.7 times the adjusted odds (95% CI 2.7, 5.2) of hospitalization with a mental health condition diagnosis, 2.7 times the odds (95% CI 1.6, 4.4) of a hospitalization with substance use disorder diagnosis, and 3.0 times the odds (95% CI 1.8, 4.8) of hospitalization with co-occurring mental health condition and substance use disorder diagnoses during the first-year postpartum. Conclusion Patients who experience SMM during their delivery hospitalization had higher odds of hospitalization with a mental health condition, substance use disorder, and co-occurring mental health condition and substance use disorder in the one-year postpartum period. Treatment and support resources for mental health and substance use providers --including enhanced screening and personal introduction of providers -- should be made available to patients with SMM upon discharge after delivery, and evidence-based interventions to improve mental health and reduce substance use should be prioritized in these patients.